DURATION LIMIT OF LASER PULSES EMITTED FROM A Ce-DOPED CRYSTAL SHORT CAVITY - Le Hoang Hai; Nguyen Dai Hung; Hoang Huu Hoa; Alex V. V. Quema; Nobuhiko Sarukura (ASEAN Journal on Science and Technology for Development, 2007)
Based on the rate equation set for broadband cavities, the dependence of pulse duration on cavity and pumping parameters is analyzed. The cavity uses a Ce-doped crystal as a gain medium. Computation results show the variation of the pulse width with the change of cavity length, mirror reflectivity, pumping energy and pumping pulse duration. A significant influence of multiple-pulse operation in limiting pulse duration is realized and a pulse-width of the order 200 ps is found to be the limit for the direct generation of ultraviolet single picosecond pulses from a Ce:LLF short cavity.